Critical and scarce: the remarkable career of limestone 1850–1914. Issue 3 (3rd May 2020) - Haumann, Sebastian
ABSTRACT: Over the past decade, the notion of 'critical raw materials' has appeared as a political concept. The reliance on these raw materials is characterized by the ambivalence of enabling future development and indicating vulnerability posed by the risks of potential scarcity. In this paper, Haumann argues that the concept of 'criticality' can be extended to historical research on resource scarcity. It highlights the importance of the construction of value added chains, analysed as dynamic technological systems, as a background for the social reflection on scarcity. As an example, the paper analyses how the use of limestone became 'critical' when it was adopted as flux in iron- and steel-making during the nineteenth and early twentieth centuries, enabling unprecedented economic growth. It stresses the interrelation of the reflection on vulnerability and scarcity on the one hand and the dynamic (re-)construction of the technological system attuned to this material on the other.